Steppe ecosystems of the arid zone of southern Russia as a factor in the effective development of livestock farming - A. I. Surov; N. G. Lapenko; O. V. Khonina; L. R. Oganyan; M. A. Starostina (Юг России: экология, развитие, 2024)
The aim of the research is to assess the current state of steppe ecosystems, which are subjected to human impact and to provide scientifically‐based proposals for the conservation and regeneration of their natural potential.The object of the study is the steppe ecosystems of the arid zone in the Stavropol Territory. The research conducted in 2019–2021 included the use of methods and techniques, encompassing the geobotanical, economic and statistical, abstract and logical, computational and constructive.An analysis of the natural resource potential of the steppes in the arid zone of Stavropol Territory showed a discrepancy between the current livestock and the carrying capacity of this territory. The forage for grazing is about 830 thousand tons of feed units, which is 1.5 times lower than the livestock needs. The predominant plant associations are wormwoodbluegrass‐sedge, bluegrass‐sheep fescue‐wormwood, bluegrass‐feather grass‐wormwood, bluegrass‐ wormwood‐salt grass with low species diversity – from 10 to 17 species per 100 m2. The plant cover of the soil is from 30 to 60 %, which indicates its sparseness. The average biological yield of phytomass is 7.0 kg/ha of air‐dry matter. The species diversity of the steppe communities is represented by weed species that have low forage quality. In natural phytocenoses, the cereals dominant in forming cenoses in virgin land, have been lost. There are no any representatives of the legume family in the plant stand.The scientific approach to sustainable development, conservation and regeneration of the potential of natural ecosystems in agricultural landscapes involves the rational use and improvement (rehabilitation) of the remaining low‐yield natural grass stands that have lost the ability of regeneration.